Analisis Partisipasi Masyarakat Terhadap Pengembangan Pariwisata Berkelanjutan (Studi Kasus di Pantai Puwakarya Desa Padak Guar Lombok Timur) - Sulaeman, Sulaeman; Alqifari, Ma’ruf (Jurnal Ilmiah Global Education, 2024)
The aim of this research is to determine the factors that hinder and support community participation in the development of the purwakarya beach tourist attraction. This research uses a qualitative descriptive method, with data collection techniques through observation, interviews and document study. This research was conducted at purwakarta beach, purwakarya hamlet, padak guar village, east lombok regency. The information in this research study consisted of 7 people who were selected using purposive sampling. Research data were analyzed using an interactive analysis model. The research results found that the factors that influence participation are divided into two, namely supporting faktors and inhibiting faktors. Supporting supporting factors are the existence of good cooperation carried out by the community in planning, implementing development monitoring funds and government support in developing this beach tourist attraction in terms of the availability of facilities and infrastructure. Meanwhile, factors that hinder the development of the purwakarya beach tourist attraction are lack of funds and low skills in making beach souvenir crafts from the community around the purwakarya beach tourist attraction.